PENGEMBANGAN MATA PELAJARAN YANG BERKAITAN DENGAN UPAYA PENINGKATAN LITERASI BUDAYA DAN KEWARGANEGARAAN - Setiawan, Budiana (Masyarakat Indonesia, 2020)
Abstract Ministry of Education and Culture in 2016 has launched The National Literacy Movement, which has been carried out in schools, families and communities. The National Literacy Movement proposes six basic literacies, namely: language, numeracy, science, digital, finances, and culture and citizenship. In this case, cultural and citizenship literacy receives less attention because it is considered lack competitive value in face of 21st century global competition. Whereas cultural and citizenship literacy is a base for formation of five basic characters, which include: religious, nationalist, independent, integrity, and mutual cooperation. The problem is what subjects can increase student awareness, especially in junior high school in supporting cultural and citizenship literacy? What aspects can be contributed from the subjects? This study is qualitative with a desk research method. Results of the study shows that subjects that are considered to increase student awareness of five basic characters, include: Social Studies, Arts and Culture, and Education for Pancasila and Citizenship. Social studies encourage students to have social awareness and be able to live together in a pluralistic society. Art and Culture as a foundation to save diverse of arts and culture of Indonesian people in facing era of modernity. Education for Pancasila and Citizenship encourages students to understand and carry out their rights and obligations as citizens of Indonesia.